Isolation, characterization and purification of xylanase producing bacteria from sea sediment. (January 2018) - Kumar, P. Senthil; Yaashikaa, P.R.; Saravanan, A.
Abstract: Xylan is the most important natural hemicellulose which has several industrial applications such as food, textile, bleaching of cellulose pulp, seed germination, degumming and agro waste treatment. Micro-organisms play a major role in the production of xylanase enzyme. In the present research, an attempt has been made to produce the xylanase enzyme from bacterial strains. The sea sediment was collected from Kovalam beach, Chennai ( Latitude : 8.4004° North, Longitude : 76.9787° East) and serial dilution was done. The serially diluted sample was plated on xylan agar medium. The isolates were characterized and identified based on morphological, biochemical and physiological characters. The zones of hydrolysis for twelve xylan utilizing bacterial isolates were obtained. Of the 12 bacterial isolates, the species obtained from the serial dilution of 10 −8 showed higher activity. The single colonies from the xylan agar plate was isolated and grown in nutrient broth supplemented with xylan in shake flask. The culture medium was centrifuged and the supernatant was used as crude enzyme. The enzyme partially purified to homogeneity by a combination of Ammonium-sulphate precipitation and dialyzed using culture supernatant as crude enzyme. The activity of the enzyme xylanase was assayed by DNSA method. The enzyme was optimally active at temperature 55 ºC and pH 9.0. The enzyme showed 95%, 90%, and 85% thermal stability at 55 °C, 60 °C and 65 °C. The enzyme was stable over a broad pH range of 8.0–10.0. Graphical abstract: fx1 Highlights: Xylan – hemicellulose was isolated and screened from bacterial strains. Xylanase purification was performed by ammonium sulphate precipitation. Residual activity of purified xylanase was determined as a function of temperature and pH. Xylanase was active at 55 °C and at the pH of 9.0. Activity of the xylanase was assayed by DNSA method.